TÁCH DÒNG VÀ BIỂU HIỆN ĐOẠN GEN MÃ HÓA VÙNG QUYẾT ĐỊNH KHÁNG NGUYÊN 56 KDA CỦA VI KHUẨN ORIENTIA TSUTSUGAMUSHI TRONG ESCHERICHIA COLI - Bùi, Thị Lan Anh; Nguyễn, Văn Minh; Trịnh, Văn Toàn; Bùi, Thị Thanh Nga; Võ, Viết Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CLONING AND EXPRESSION OF DETERMINANT REGION OF 56 KDA TYPE-SPECIFIC ANTIGEN OF ORIENTIA TSUTSUGAMUSHI IN ESCHERICHIA COLI The 56-kDa type-specific antigen is a major outer membrane protein located on the surface of Orientia species. This 56-kDa antigen has widely applied for evaluation and diagnosis of scrub typhus. However, these antigens are diversity among serotype. Therefore, most of diagnostic test for scrub typhus must be a combination of all types of 56 kDa antigens. In the previous study, we found that the most common genotype was identified in Vietnam belong to Karp, Kato, TA763, Gilliam genotypes. In order to create an ELISA kit for diagnose scrub typhus in Vietnam, these common genotypes are cloned and expressed in E. coli cells for producing recombinant proteins. In this study, a determinant antigen of 1149 bp gene encoding for 56 kDa antigen specific to Karp serotype of O. tsutsugamushi was cloned into pET22b(+) plasmid and expressed in E. coli BL21(DE3) cells. The result indicated that the truncated 56 kDa antigen was successfully expressed in E. coli BL21 cells by inducing with 0.5 mM IPTG in 4 hours. Western blotting showed that HT09 protein reacted with the antiserum against O. tsutsugamushi. This recombinant HT-09 protein is able to use as a specific antigen for developing O. tsutsugamushi diagnostic.